Effect Of Good Corporate Governance On Company Profitability RE & Property Sector In Indonesia - Mohammad Hamim, Ahmad Azmy, Dea Restiya Anggreini, (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
This study aims to examine the effect of Good Corporate Governance (GCG) on company profitability. The dependent variable are Return On Assets (ROA) and Return On Equity (ROE). The independent variable are Good Corporate Governance (GCG) represented by the Board of Commissioners, the Board of Directors, and the Audit Committee. This study uses secondary data from audited financial statements of Real Estate and Property companies in 2013-2017. The analytical tool used in this study uses panel data regression. Based on the results of the study it is known that the Board of Directors and Audit Committee variables have a significant positive effect on ROA and ROE. The Board of Commissioners variable has no influence and negative relationship to ROA and ROE.